2016
DOI: 10.2807/1560-7917.es.2016.21.9.30154
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus detection in urine from patients with Guillain-Barré syndrome on Martinique, January 2016

Abstract: We report two cases of Guillain–Barré syndrome who had concomitant Zika virus viruria. This viruria persisted for longer than 15 days after symptom onset. The cases occurred on Martinique in January 2016, at the beginning of the Zika virus outbreak. Awareness of this possible neurological complication of ZikV infection is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 7 publications
2
78
0
5
Order By: Relevance
“…Up to present, studies describing the role of ZIKV in GBS have focused on outbreak areas and symptomatic ZIKV patients 4, 5, 8, 9, 25, 26, 27. Interestingly, ZIKV infections are symptomatic in only an estimated 20% of cases and ZIKV will probably soon be endemic in most affected areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to present, studies describing the role of ZIKV in GBS have focused on outbreak areas and symptomatic ZIKV patients 4, 5, 8, 9, 25, 26, 27. Interestingly, ZIKV infections are symptomatic in only an estimated 20% of cases and ZIKV will probably soon be endemic in most affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…The first study reporting on the association between ZIKV and GBS indicated that ZIKV infections were exclusively associated with axonal GBS, whereas recent reports from Brazil and Colombia show that AIDP is the subtype of GBS associated with ZIKV infection 5, 8, 25, 26, 27. Some of this variety may be attributed to retrospective analysis of nonstandardized clinical and electrophysiological data to describe subtypes of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ZIKV is detectable for a longer time frame post-infection in urine than serum (7 or more days after becoming undetectable in serum) [38] and at a higher viral load in urine (up to 220 × 10 6 copies/mL) than in corresponding serum samples (up to 8.1 × 10 6 copies/ mL) [42]. Other groups have also reported either a longer detection window or an increased ZIKV detection in urine over other bodily fluids on a case study basis (Tables 1 and 2) [30,37,[43][44][45][46], although there have been cases where ZIKV was detected in the serum but not urine [47]. A larger cohort of paired serum and urine samples would be beneficial to support these findings.…”
Section: Advantages Of Non-invasive Sample Collectionsmentioning
confidence: 99%
“…Although acute coinfection with DENV and ZIKV cannot be ruled out on the basis of the diagnostic tests performed, the finding of ZIKV in the urine confirms the diagnosis of ZIKV-associated GBS. 28,29 The fact that his serum PCR was negative for ZIKV on day 4 of illness but urine PCR was positive on day 18 is not surprising; viral persistence in urine has been documented in multiple prior studies. 30,31 The viremia associated with ZIKV infection is thought to be relatively low titer and short lived, lasting only 2-3 days and waning with the onset of rash.…”
Section: Discussionmentioning
confidence: 99%